2006
DOI: 10.2214/ajr.05.1397
|View full text |Cite
|
Sign up to set email alerts
|

Digital and Screen-Film Mammography: Comparison of Image Acquisition and Interpretation Times

Abstract: Compared with screen-film mammography, the use of digital mammography for screening examinations significantly shortened acquisition time but significantly increased interpretation time. In addition, more technical problems were encountered that delayed the interpretation of digital cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 7 publications
2
46
1
Order By: Relevance
“…However, soft-copy reading using the The overall mean kappa value is based on all 42 pair of comparisons for the seven radiographers enhancement tools increases the interpretation time of digital mammograms. 5 Pisano et al reported no significant difference in the interpretation time between printed digital mammograms and soft-copy reading, but they emphasized that appropriate training for soft-copy reading and soft-copy workstations must therefore become more user-friendly. 14 As a result, soft-copy workstations have recently improved and indeed become more user-friendly; and the workstations have developed advanced image-processing algorithms to equalize the image background and breast tissue thickness to reduce the interpretation time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, soft-copy reading using the The overall mean kappa value is based on all 42 pair of comparisons for the seven radiographers enhancement tools increases the interpretation time of digital mammograms. 5 Pisano et al reported no significant difference in the interpretation time between printed digital mammograms and soft-copy reading, but they emphasized that appropriate training for soft-copy reading and soft-copy workstations must therefore become more user-friendly. 14 As a result, soft-copy workstations have recently improved and indeed become more user-friendly; and the workstations have developed advanced image-processing algorithms to equalize the image background and breast tissue thickness to reduce the interpretation time.…”
Section: Discussionmentioning
confidence: 99%
“…Soft-copy reading using the enhancement tools results in increasing the interpretation time of digital mammograms. 5 Softcopy workstations have improved over the years to become more user-friendly. In addition, the workstations have developed advanced image processing algorithms to equalize image background and breast tissue thickness and to highlight specifi c features such as microcalcifi cations to reduce the interpretation time.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the advantages of digital mammography are related to getting rid of film. With integrated digital systems, the lack of film cassette handling allows for a higher patient throughput [54] and lets the technologist concentrate more on the patient. Especially interventional procedures such as preoperative wire localizations are much faster with integrated digital systems without the need for films to be developed between each step of the procedure.…”
Section: Impact On Workflowmentioning
confidence: 99%
“…Approximately 7% of US mammography practices had at least one digital system as of April 2005 1 . That percentage has risen gradually to 43% by October 2008 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Two European studies have recently confirmed a diagnostic advantage for digital mammography 5,6 . An offsetting disadvantage is that digital screening mammograms (DM) take longer to interpret than film-screen screening mammograms (FSM) 1,7 . Previous studies have not, however, evaluated what part or parts of the process of interpreting DM causes the expenditure of extra time.…”
Section: Introductionmentioning
confidence: 99%